2021
DOI: 10.1016/j.energy.2020.119341
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study on the CO2 gasification of biochar derived from Miscanthus at different processing conditions

Abstract: CO 2 gasification is an emerging process that can improve the quality of syngas and enhance the CO 2 circular utilisation. This paper presents an analysis on the CO 2 gasification of Miscanthus-derived biochar produced at various processing conditions. The gasification behaviour, kinetics and biochar reactivity were investigated and the correlations to the biochar preparation condition and their microstructure were developed. Results showed that the preparation and gasification reaction conditions had major im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…The above values also confirmed that decomposition of the torrefied hops waste sample is more complex. The values for the miscanthus sample are in agreement with those in the literature [97,100]. Likewise, for hops waste samples no experimental data have been found yet.…”
Section: The Pre-exponential Factorsupporting
confidence: 91%
See 1 more Smart Citation
“…The above values also confirmed that decomposition of the torrefied hops waste sample is more complex. The values for the miscanthus sample are in agreement with those in the literature [97,100]. Likewise, for hops waste samples no experimental data have been found yet.…”
Section: The Pre-exponential Factorsupporting
confidence: 91%
“…The values were within the range of 14-224 kJ/mol and 60-221 kJ/mol for the Friedman and KAS models, respectively. The literature survey showed that the average activation energies for raw miscanthus reported in the literature are between 78 and 212 kJ/mol (determined by several kinetics models, including the KAS/FR methods) [97][98][99], which is close to the values achieved in this study. For instance, the activation energies reported by Cortés and Bridgwater [100] for raw and torrefied miscanthus were in the range of 129 to 156 kJ/mol using the same isoconversional models.…”
Section: Activation Energysupporting
confidence: 88%
“…The third-order kinetic model is rarely applied in biochar chemistry. However, Zahedifar and Moosavi [181] reported that it was unsuitable to explain the Zn desorption mechanisms from biochar-amended calcareous soils, while Tian et al [182] showed that the third-order kinetics can be efficaciously used to describe the mechanisms of the CO 2 gasification of Miscanthus-derived-biochar at different processing conditions.…”
Section: The Kinetics Of Biochar Adsorption/desorptionmentioning
confidence: 99%
“…25,44 Precisely, the pyrolysis rate, pressure, and thermal pre-treatment of the biomass also play a crucial role in the process. [45][46][47] While pyrolysis, especially the denoted intermediate pyrolysis, is the most used process, several other methods were reported such as hydrothermal carbonization, 48,49 high-temperature gasification, 50,51 or the microwave-assisted pyrolysis. 52 The primary research efforts should focus on the most efficient use of each type of biomass to obtain maximum yield and quality, as well as the most cost-effective ratio of these three products.…”
Section: Introductionmentioning
confidence: 99%